Pengaruh Electronic Word of Mouth, Credibility Celebrity Endorser, dan Visibility Celebrity Endorser Dewi Sandra terhadap Brand Image Wardah Cosmetics (Studi Kasus Mahasiswi Fakultas Ekonomi dan Bisnis Universitas YARSI) - Ainun Nadhiroh; La Diadhan Hukama (JURNAL PUNDI, 2019)
The purpose of this study was to determine the effect of electronic word of-mouth (eWOM), celebrity endorser credibility, and visibility celebrity endorser Dewi Sandra on brand image formation of Wardah Cosmetics for student in Faculty of Economics and Business, YARSI University. The analytical method used is descriptive analysis and multiple linear regression. The results of this study indicate that electronic word of-mouth (eWOM) and Credibility Celebrity Endorser have a positive and significant influence on brand image formation of Wardah Cosmetics. Meanwhile, Visibility Celebrity Endorser has a negative and not and not significant on brand image formation of Wardah Cosmetics.